Investigating the value preferences among in-school adolescents in Nigeria - Joseph, Thomas P.; Engku Kamarudin, Engku Mardiah; Roslan, Samsilah; Zaremohzzabieh, Zeinab (Gokmen Arslan, 2022)
This study aims to investigate the value preferences of in-school adolescents. The study employed a survey design. The population was 2803 in-school adolescents in the senior secondary II in the urban and rural in the Ankpa education zone of Kogi State, Nigeria. Then, 280 senior secondary II was used as a sample through multistage sampling techniques. The value preferences of in-school adolescents questionnaire (VPOAQ) instrument developed was used to collect the data. Mean scores and standard deviations were used to answer the research questions while one-way ANOVA was used to test the null hypotheses. The study found that both male and female in-school adolescents have preferences for the same values like fulfillment, family life, competitiveness, creativity, religion, and hard work except friendliness and leadership irrespective of their locations. Despite the multicultural nature of our society, there is a core value that is undisputable anywhere in the world but is rapidly being eroded, hence, constant enlightenment campaigns on core values should be carried out in our towns, villages, and cities to help educate and guide the adolescents on value-related issues.